A new type of PHC pile-sinking technology: Drilling with PHC Pipe Cased Pile and its development directions. Issue 1 (October 2020) - Hou, Zhenkun; Tang, Mengxiong; Hu, Hesong; Lin, Zegeng; Chen, Yining; Zhao, Shiyuan; Zhang, Shuo
Abstract: Pile foundation has unique advantage in reducing the settlement of the upper structure and improving the foundation bearing capacity, while Drilling with PHC Pipe Cased Pile (DPC Pile) is a newly developed non-extruded soil PHC tubular pile which integrates drilling-pile sinking-dumping simultaneously to solve the pile sinking problem of large diameter (800 ∼ 1400mm) pipe pile. It solves the problem of pile sinking caused by large pile diameter or hard soil layer, breaks the situation that the pipe pile foundation can only be limited to small diameter and size, and broadens the applicable scope of engineering geology of pipe pile. It realizes the full rock-socketed of the pile tip (which can enter the middle and weak weathering stratum), improves the bearing capacity of single pile, and gives full play to the advantages of pipe pile material with higher strength. It has little damage to the pipe pile and little noise, being relatively environmentally friendly, as well as plays a major demonstration role in leading the new direction of the development of green, energy-saving and environmental protection pile foundation, conforming with the advanced development trend of upgrading traditional advantageous industries to high-tech manufacturing and construction technology with promising market.